Synthesis and application of new solid phase techniques in quantitative proteomics using MALDI and ESI mass spectrometry - Moschidis, Petros; Giovanni Sindona, Giovanni; Gabriele, Bartolo (My University, 2008)
Proteomics, the analysis of the protein complement of a cell or an organism has grown rapidly as a category of the life sciences. Mass spectrometry (MS) is one of the central detection techniques in proteome analysis, yet it has to rely on prior sample preparation steps that reduce the enormous complexity of the protein mixtures obtained from biological systems. For that reason, a number of tagging (or labeling) strategies have been developed that target specific amino acid residues or post-translational modifications, enabling the enrichment of subfractions via affinity clean up, resulting in the identification of an ever-increasing number of proteins. In addition, the attachment of stable isotope-labeled tags now allow the relative quantitation of protein levels of two samples, e.g. those representing different cell states, which is of great significance for drug discovery and molecular biology. This work presents the research for new stable isotope-labeled (as well as stable-isotope free) solid phase strategies for the identification and relative quantitation of complex protein mixtures using MALDI and ESI-MS, MS/MS technology.
Dottorato di Ricerca in: Methodologies for the development of molecules of pharmacological interest, Ciclo XXI,a.a. 2007-2008
Keywords: Chimica; ecniche di analisi della materia; Spettrometria di massa